Dono, ospitalità, democrazia - Fistetti, Francesco (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2016)
Developing itself under the sign of neoliberalism and working for the sole pursuit of economic profit (with results whose evidence is there for everyone to see), the globalization of capitalism challenges our political thought. We need to understand that carrying on along the path of unlimited growth and according to today's dominant paradigms, we can witness a worsening of a situation that is already clearly unsustainable. The paradigm of gift, as identified by Mauss in his accusation of the “homo oeconomicus”, can be now the backbone of a new and “lateral” form of universalism (Merleau-Ponty). That is, for a sort of “pluriversalism” in which human affections and passions can acquire a new centrality, helping us in a re-institutionalization of the public space. Giving to our time a comprehensive vision of history, the new philosophy that we can call “convivialism” allow us to understand and live the global era, whit its endless alterations but also with its great opportunities. Keywords: Globalization; Gift; Mauss; Convivialism.